Dielectrophoresis of Tetraselmis sp., a unicellular green alga, in travelling electric fields analyzed using the RC model for a spheroid - Sakshin Bunthawin (Songklanakarin Journal of Science and Technology (SJST), 2011)
Dielectrophoresis of a unicellular green alga, Tetraselmis sp., in a travelling electric field was analyzed using an RC(resistor-capacitor)-model, instead of the Laplace approach reported in our previous work. The model consists of resistorcapacitorpairs in series to represent the conductive and the capacitive properties of the shell and the inner part of the spheroid.The model is mathematically simpler than the Laplace model and the RC approach is experimentally superior because only thelower critical frequency [LCF] and cell translational speed are required to be measured experimentally. The effective compleximpedance of the spheroid was mathematically modeled to obtain the Clausius-Mossotti factor ([CMF]) as a function of celldielectric properties. Spectra of dielectrophoretic velocity and the lower critical frequency of the marine green alga, Tetraselmissp. were investigated to determine cell dielectric properties using a manual curve-fitting method. Effects of arsenic at differentconcentrations on the cell were examined to verify the model. Arsenic severely decreases cytoplasmic conductance (c)whereas it increases membrane conductance (m). Effects were easily observable even at the lowest concentration of arsenicused experimentally (1 ppm). The method offers a practical means of manipulating small plant cells and for rapid screeningfor effects on the dielectric properties of cells of various applied experimental treatments.